Adaptation of the Godin Leisure-Time Exercise Questionnaire into Turkish: The Validity and Reliability Study. (31st July 2016) - Sari, Emine; Erdoğan, Semra
Abstract : This study was conducted with the aim of determining whether the Turkish form of the "Leisure-Time Exercise Questionnaire" developed by Godin is a valid and reliable tool for diabetic patients in Turkey. The study was conducted as a methodological research on 300 diabetic patients in Turkey. The linguistic equivalence of the questionnaire was assessed through the back-translation method, while its content validity was assessed through obtaining expert opinions. Cronbach's alpha value was found to assess the reliability of the questionnaire. The test-retest analysis and the correlation between independent observers were examined. The content validity index (CVI) was found to be .82 according to the expert assessments, and no statistical difference was found between them (Kendall'sW = . 17, p = . 235 ). Cronbach's alpha was found to beα = . 64, the result of the test-retest analysis wasr = . 97, and the correlation between independent observers (ICC) was .98. This study found that the Turkish form of the Leisure-Time Exercise Questionnaire is a valid and reliable tool that can be used to define and assess the exercise behaviors of Turkish diabetic patients.